Effect of a combination of gastrin, secretin, cholecystokinin, glucagon, and gastric inhibitory polypeptide on jejunal absorption in man. Issue 4 (April 1980) - Poitras, P; Modigliani, R; Bernier, J J
Abstract : In 11 conscious volunteers, the jejunal absorption was measured during basal state and during the simultaneous intravenous infusion of small doses of gastrin, secretin, cholecystokinin, glucagon and gastric inhibitory polypeptide. The blood levels of gastrin, secretin, glucagon, and GIP were measured by RIA and were close to those achieved after a meal. The basal net absorption of water and electrolytes was reversed to a net secretion during the hormonal infusion. These results suggest that the jejunal secretion observed after a meal in man may be mediated by hormones released by the meal.